Victorian life - Guy, John. (Tunbridge Wells, England : Ticktock Publishing, 2004)
Color illustrations and brief descriptions present British life for the rich and poor in the age of Queen Victoria, covering town and country life, food and drink, pastimes, fashion, art and architecture, health and medicine, love and marriage, women and children, war and weaponry, crime and punishment, transportation and science, and religion.
Includes index.
8.1
5-8
Keywords: Great Britain -- History -- Victoria, 1837-1901.; Great Britain -- Social conditions -- 19th century; Great Britain -- Social conditions; Great Britain -- History -- 19th century